THE CAMBRIDGE INTRODUCTION TO INTERCULTURAL COMMUNICATION: BY GUIDO RINGS & SEBASTIAN M. RASINGER, CAMBRIDGE UNIVERSITY PRESS, 2023 - Tallone, Laura (POLISSEMA – Revista de Letras do ISCAP, 2023)
Recensão cr´ítica do livro, recentemente publicado, The Cambridge Introduction to Intercultural Communication, de Guido Rings & Sebastian M. Rasinger, Cambridge University Press, 2023